Joyce Molyneux and Gerard Baker: Born to Cook: Angel Food - Storey, Jennifer (Petits Propos Culinaires, 2012)
Joyce Molyneux and Gerard Baker: Born to Cook: Angel Food: Adam White, 2011, 149 pp., paperback, £14.95.